EFEK OREINTASI KEWIRAUSAHAAN, INOVASI DAN MANAJEMEN PENGETAHUAN TERHADAP KINERJA ORGANISASI PELAKU UMKM DI KABUPATEN SUMENEP - -, Minullah; rahman, fathor; -, Liyanto (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2024)
In the midst of increasingly fierce and competitive business competition, organisations need to develop strategies and practices that drive competitive advantage. This study aims to analyse the effect of entrepreneurial orientation, innovation, and knowledge management on organisational performance. Using associative quantitative methods, data was collected through questionnaires distributed to 66 umkm. Data analysis was conducted using multiple linear regression to test the influence of each variable on organisational performance. The analysis results show that the entrepreneurial orientation variable has a t coefficient of 0.307 with a significance value of 0.760. Since this significance value is greater than 5% (sig. > 5%), it can be concluded that entrepreneurial orientation partially has no significant effect on organisational performance. In contrast, the innovation variable shows a t coefficient of 3.868 with a significance value of 0.000, which means that innovation has a significant positive effect on organisational performance (sig. < 5%). This confirms that the organisation's ability to innovate is a key factor in improving efficiency, effectiveness, and competitiveness. In addition, the knowledge management variable has a t coefficient of 3.625 with a significance value of 0.001, indicating a significant positive effect on organisational performance (sig. < 5%). Effective knowledge management supports better decision-making processes and continuous innovation, which in turn improves organisational performance. Thus, the results of this study underscore the importance of innovation and knowledge management as key factors contributing to improved organisational performance, while entrepreneurial orientation showed no significant influence in the context of this study. These findings provide insights for practitioners and academics to focus more efforts on developing innovation and knowledge management in order to achieve optimal organisational performance optimal